Machalilla, Ecuador. Die letzten Reste des eponymen Fundortes der formativen Machalilla-Kultur. Die Arbeiten der Jahre 2017 und 2018 - Prümers, Heiko; Ugalde, María Fernanda (e-Forschungsberichte des DAI, 2018)
Starting in 2017, archaeological investigations were carried out in Machalilla, the type-site of the Middle-Formative Period Machalilla Culture (1400–800 BC) on the Ecuadorian coast in southern Manabí. Since 1958, when the Ecuadorian archaeologist Emilio Estrada defined this culture, not a single settlement of the Machalilla Culture has been satisfactorily excavated and documented. So the aim of our project was to fill this gap and to study the relationship of the Machalilla Culture to earlier Valdivia and posterior Chorrera-Cultures. Our excavations provided a solid sample of ceramics, lithic and shell artefacts from the three formative cultures that is still under study.